Renal Cell Cancer: Clinicopathological Profile and Survival Outcomes - Tiwari, Priya; Kumar, Lalit; Singh, Geetika; Seth, Amlesh; Thulkar, Sanjay (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: The incidence of renal cell cancer (RCC) is increasing worldwide. However, scant information is available from the Indian subcontinent regarding its clinicopathological characteristics and survival outcomes. We retrospectively analyzed data of patients suffering from RCC at our center over the last one decade (2004–2013) to generate information on these aspects. Materials and Methods: Case records of 423 patients treated between 2004 and 2013 were retrospectively analyzed. Baseline characteristics, histopathological information, and survival outcomes were assessed. Overall survival was calculated from the time of diagnosis to death due to any cause. Results: The median age was 52 years (range: 18–87 years). Male: female ratio was 3.5:1. The median duration of symptoms was 3 months (range: 0–24 months). Thirty-five patients (8.3%) were detected in asymptomatic state. The most common symptom was hematuria (53.2%) followed by flank pain (46.3%). The most common histology was clear cell subtype (71.4%). Two hundred and ninety-three (69.3%) patients presented with nonmetastatic disease whereas 130 (30.7%) had upfront metastatic disease. Five-year survival in Stages 1, 2, 3, and 4 was 92.7%, 72.9%, 54.6%, and 11.5%, respectively. Conclusion: Younger age, higher male–female ratio, lower proportion of asymptomatic patients, higher proportion of advanced stage at diagnosis, and lower stage-wise survival were some of the key findings.
Keywords: Clear cell; hematuria; renal cell cancer